Socio-Political Criticism of the New Order in the Interpretation of Syu'bah Asa - Miftahul Umam (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
In this study, the author explains the contribution of Syu'bah Asa in the Qur'an interpretation in Indonesia through his work, Dalam Cahaya Al-Qur’an: Tafsir Ayat-ayat Sosial Politik, a contextual socio-politics interpreting of the New Order government. The discourse in this interpretation was developed in a critical, straightforward, and bold content, aiming at a critique of various misappropriations during the New Order. This research is a literature study with descriptive analysis methods, which helps the author see Syu'bah Asa’s knowledge metamorphosis, approach, socio-political criticism, and interpretations’ contribution to the intellectual development of Islam in Indonesia. The results of this study confirm that the text of the Qur'an should be read in a social context when the Qur'an is derived, which helps us to find the moral legality of a verse that can be applied in socio-political dynamics that are constantly changing. The critical interpretation carried out by Syu'bah Asa is one of the slick examples of various contextual interpretations. Syu’bah Asa’s work has contributed to an understanding of socio-political dynamics in Indonesia, which at that time was not much explored.